Federal construction contracting made easy - Uhlig, Stan (Management Concepts, 2012)
Follow the Path to Success in Federal Construction ContractingOpportunities abound in federal government construction contracting, but the devil is in the details. Companies performing work for the federal government must plan and operate based on very specific guidelines and regulations. Knowing how to work within those strict parameters makes the difference between success and failure.Federal Construction Contracting Made Easy is your road map to successfully identifying, planning, and completing government construction projects. This book guides you in finding opportunities, preparing winni.